Analysis of The Potential Banana Prawn (Penaeus merguiensis) in The Northern Waters of Rembang Regency - Muhamad Fathikul Umam; Agus Suherman; Kukuh Eko Prihantoko (Bogor Agricultural University, 2021)
This study aims to describe the characteristics of mini bottom trawl fishing gear and fishing season, as well as to estimate the stock density and sustainable potential of banana prawn (Penaeus merguiensis), in Rembang Regency. This study was conducted from September to October 2020, in the Northern Waters of Rembang Regency, with an area of ​​1409.7 km², using both primary and secondary data. Primary data was collected directly from observations, measurements, and interviews with fishermen, while secondary data, including data on the number and types of fishing gear, as well as production and production values, was obtained through a literature review. The results of the study found that banana prawn in the northern waters of Rembang Regency was caught using two types of fishing gear, and these are sotok/mini bottom trawls and trammel nets. The total length of mini bottom trawl in this study are 15.77 m, 16.5 m, 20.44 m, and 25.2 m. The fishing season for banana prawn is from June to September The average stock density value is 16.22 kg/km² (range 4.37 to 41.14 kg/km²), the Cmsy value is 2.625 kg, the Emsy value is 4.172 trips and the average utilization rate is 44% (range 23 to 82%). Keywords: Rembang, banana prawn, stock density, and MSY.